1993
DOI: 10.7326/0003-4819-119-9-199311010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Cytomegalovirus Disease

Abstract: Internists should be aware of the various clinical settings and locations in the gastrointestinal tract in which CMV disease occurs. Patients with immune deficiency and gastrointestinal signs and symptoms should have imaging tests and mucosal biopsies to investigate the possibility of CMV intestinal disease. Treatment with antiviral chemotherapy improves outcome in many patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
246
5
6

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 401 publications
(265 citation statements)
references
References 0 publications
8
246
5
6
Order By: Relevance
“…Based on the outcome of our case, when progressive pancytopenia is observed during cyclophosphamide treatment for SLE, a bone marrow aspiration should be performed at an early stage to identify the cause of pancytopenia. The occurrence of CMVdisease in the gastrointestinal tract has been recently noted in immunocompromised hosts (9), such as AIDS patients (10, 1 1), transplant recipients and patients receiving immunosuppressive therapy ( 1 2). In addition, inflammatory bowel diseases, such as ulcerative colitis and Crohn's disease, are frequently complicated by this disease (1 3).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the outcome of our case, when progressive pancytopenia is observed during cyclophosphamide treatment for SLE, a bone marrow aspiration should be performed at an early stage to identify the cause of pancytopenia. The occurrence of CMVdisease in the gastrointestinal tract has been recently noted in immunocompromised hosts (9), such as AIDS patients (10, 1 1), transplant recipients and patients receiving immunosuppressive therapy ( 1 2). In addition, inflammatory bowel diseases, such as ulcerative colitis and Crohn's disease, are frequently complicated by this disease (1 3).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that CMV may cause endothelial disruption, creating a favourable environment for extrapulmonary P carinii infection (15). Alternatively, it has been suggested that CMV can secondarily infect tissue with rapid growth such as endothelial cells in inflammatory tissue (21). If this hypothesis is true, then the situation would be reversed -the presence of CMV would be secondary to the effect of the primary P carinii infection.…”
Section: Discussionmentioning
confidence: 97%
“…Megacólon tóxico fatal por cytomegalovirus em paciente com retocolite ulcerativa idiopática: relato de caso e revisão de literatura A análise histopatológica define o diagnóstico, sendo caracterizada por células infectadas com tamanho de 25 a 35 µm de diâmetro, contendo inclusão eosinofílica intranuclear, rodeada por halo claro e cromatina granular, além da possível associação com inclusões citoplasmáticas basofílicas (5) . A utilização de anticorpos monoclonais anti-CMV por meio de técnicas como a imunoperoxidase e imunofluorescência, e a hibridização in situ aumentam a sensibilidade da análise histopatológica.…”
Section: Discussionunclassified